Cambios estacionales en las muertes por categorías y sus causas en bovinos lecheros de la provincia de Camagüey, Cuba - Pérez-Castro Basulto, María Lucía; Bertot Valdés, José Alberto; Vázquez Montes de Oca, Roberto; Garay Alvarez, Godofredo Ramón (Revista de Producción Animal, 2024)
Nota Técnica